IoT-Based Automated Catfish Feeder Applicatoin: A Case Study at Dompon Sejahtera Fishery - Kisan Rozin Asrigen; Rr. Hajar Puji Sejati (Komunitas Dosen Indonesia, 2025)
Conventional catfish aquaculture in Indonesia often suffers from inefficient feed management due to manual feeding, leading to feed waste, poor water quality, and inconsistent fish growth. To address these limitations, this study develops a user-friendly Internet of Things (IoT)-based automatic catfish feeding system that integrates automation, real-time monitoring, and simplified configuration. The system employs an ESP32 microcontroller as the core hardware and Firebase as a cloud-based backend for instantaneous data synchronization. A key innovation is the inclusion of a local web server on the ESP32, enabling farmers to configure Wi-Fi networks directly through a browser without reprogramming the device. The companion mobile application, “Feedy Finn,” built using Flutter, allows users to remotely set feeding schedules, control operations manually, and monitor device performance in real time. Black Box testing demonstrated stable two-way communication with a latency of under 500 milliseconds and a feed dispensing consistency exceeding 95%, reducing feed waste by approximately 20% compared with manual methods. The results confirm that the system enhances operational efficiency, ensures precise feeding intervals, and simplifies device setup, making it accessible to small and medium-scale fish farmers. Beyond technical performance, the study contributes to sustainable aquaculture by minimizing environmental impact and promoting digital inclusion in rural communities. This integration of affordability, usability, and automation highlights the system’s potential as a scalable model for advancing smart aquaculture and supporting Indonesia’s transition toward technology-driven fisheries.